Determinación de la actividad antimicrobiana de Peperomia galoides H.B.K «Congona» - Rossi Cortez, César A. (2003)
It has been determined the antimicrobial activity of Peperomia galoides H.B.K. medicinal plant from Callejon de Huaylas using the diffusion disk plate method. The different extracts from this plant were assayed against Gram-positive bacteria, Gram-negative bacteria and one yeast. This plant showed antimicrobial activity against gram positives bacterias.